GLOBAL GEOGRAPHICAL DIFFERENTIATION OF LATE CRETACEOUS AND CENOZOIC FLORAS AGAINST THE BACKGROUND OF GEOLOGICAL AND OTHER ABIOTIC EVENTS - Akhmet'ev M.A. (My University, 1999)
Principal geological and paleogeographic events of the Late Cretaceous time are considered. Movements of continental blocks, changes in oceanic and atmospheric circulation, and interrelated climatic fluctuations during the last 100 m.y. were the main factors responsible for the geographical flora differentiation. The origin and transformation basis of phytochoria boundaries are also discussed along with the influence of paleoand neoendemics upon the geographical flora differentiation. In addition, the phytochoria tree branches established earlier (Meyen, 1987; Vakhrameev, 1988) are used as a basis of a general model describing all Phanerophytic floras and projecting the principal tree stems to the current phytochoria system suggested by Takhtadzhyan (1978). The generation and evolution history of certain kingdoms and subkingdoms is considered. Certain attention was focused on changes in the main tree stems as related to global ecological crises in the past, which produced a considerable impact on the taxonomic diversity of terrestrial floras. The possibility of using the paleobotanical data to correct and check independently the tectonic and paleogeographic reconstructions is demonstrated.
Keywords: Cretaceous; Cenozoic; Кайнозой; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic